Variability of the Folin-Denis method in the determination of tannic acid equivalents in sorghum samples (Semiárida, 2020)
The purpose of this work is to evaluate the influence of some factor that condition the variability of the Folin-Denis method to determine de equivalents of tannic acid in grain of sorghum. We studied the influence of the centrifugation previous to the spectrophotometric measurement. It was also studied the most convenient refluxed time for the extraction of tannic substances. The application of centrifugation to the aqueous extract after a night rest showed highly significant differences (p< 0,01) with respect to the sample without centrifugation. Considering both procedures, we got "r" 0,997 and the equation of regressi0n responds to y = 0,0627 + 1,033 x. The coefficient of variations fluctuates between 1,94 and 5,77 % for samples without centrifugation and between 0,71 and 3,85 % for samples with centrifugation. Therefore, in order to decrease the variability of the methods it is convenient to apply a ten-minute centrifugation at 5.000 rpm to the aqueous extract. It was determined that for the refluxe time there are no differences of extraction between 2 and 5 hours, though it tends to increase as time increases. For routine determinations a 3 hours refluxe extraction is enough but 5 hours are advisable for greater precision.